Lead Poisoning in Children Younger than 6 years Old From Rural Areas of Callao - López Sandoval, Jorge (2000)
OBJECTIVES: To determine the lead serum levels among children from a rural area where there were three cases of severe neurological involvement in children attributable to lead poisoning, in order to establish a possible relationship with toxic levels of lead environmental contamination. MATERIAL AND METHODS: An observational, cross sectional trial, in which lead serum levels were assayed in children from "Puerto Nuevo", a rural and poor-income area of Callao harbor, Lima, Peru. Capillary blood samples were assayed through the anode voltametry method. RESULTS: A total of 136 children were evaluated, 69 were females and 67 males. There were no differences in serum lead levels between males and females. The mean values found were the following: 9,54 ± 4,48 gg/dL (<6 months), 19,47 -t: 9,03 gg/dL (7-12 months), 28,76.t 9,74 gg/dL (1-year-old), 31,36 -t 12,30 gg/dL (2-years-old), 28,96±10,56 gg/dL (3-years-old), 29,08 a, 11,40 gg/dL (4-years-old) and 32,98.t: 11,12 gg/dL (>5 years). CONCLUSIONS: Prevalence of lead poisoning is high among the evaluated children and is related to their age, which means, to the time of environmental exposition.